Pengembangan Kreativitas Mahasiswa melalui Pelatihan Totebag Ecoprint sebagai Produk Sustainable Fashion Bernilai Jual - Anggit Dyah Kusumastuti; Hanifah Nur Aisyah (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity was conducted for students of the Business Administration Study Program at Universitas Sahid Surakarta with the aim of improving creativity and innovation through the production of ecoprint totebags as sustainable fashion products with economic value. The activity was carried out through counseling, demonstrations, and direct practice using natural materials such as leaves and flowers from the surrounding environment. Initial observations showed that most participants had limited understanding of sustainable fashion and ecoprint techniques. After the activity, the post-test results indicated an increase in participants’ understanding of sustainable fashion from 25% to 88% and understanding of ecoprint techniques from 30% to 90%. In addition, 85% of participants expressed interest in developing ecoprint products as creative business opportunities. The ecoprint totebags produced had unique motifs, aesthetic value, and potential as environmentally friendly fashion products. This activity successfully improved students’ skills and awareness regarding the importance of developing creative products based on environmental sustainability. Therefore, this activity can support the development of environmentally sustainable creative entrepreneurship among students.